Ecos e vozes do cotidiano da EJA: identificando falas dos alunos na Baixada Fluminense - RJ - Silva, Tania Maria Almenara da (2011)
This study was conducted at the Municipal School Manoel Reis, in the municipality of Mesquita, Baixada Fluminense-RJ. From interviews with students of EJA, we investigate: the expectations about the course, his vision of education, the contradictions in relation to its structure and what students look at AYE and the materialization of the Pedagogy of Hegemony. We found that the school is often identified with the space and time manufacturing. We understand that in most cases, the student of the EJA is low-income worker with serious social problems. However, listening to them we can glimpse structures courses that meet their expectations. We intend to collaborate to understand the specifics of the EJA and its subjects in their real needs, and training not linked to market logic, which enter the student role in this process. Thus, for education as a practice of freedom, as we said Freire (2008), it is necessary to hear the echoes of voices silenced. However, the logic of capital is a societal need to conform the masses that Lucia Neves called Pedagogy of hegemony, Gramsci making category. We aim also to observe how it is produced daily at school through the words of students.